2023
DOI: 10.1177/0271678x231169579
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin and cerebral hypoxic vasodilation in humans: Evidence for nitric oxide-dependent and S-nitrosothiol mediated signal transduction

Abstract: Cerebral hypoxic vasodilation is poorly understood in humans, which undermines the development of therapeutics to optimize cerebral oxygen delivery. Across four investigations (total n = 195) we investigated the role of nitric oxide (NO) and hemoglobin-based S-nitrosothiol (RSNO) and nitrite ([Formula: see text]) signaling in the regulation of cerebral hypoxic vasodilation. We conducted hemodilution (n = 10) and NO synthase inhibition experiments (n = 11) as well as hemoglobin oxygen desaturation protocols, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…There is evidence that hypoxia-induced increases in cerebral blood flow are mediated by NO. 6 , 14 We found that in our experimental conditions, hypoxia-induced dilations of cortical arterioles in response to 10% inspired O 2 were unaffected by systemic NO synthase (NOS) blockade with N(ω)-nitro-L-arginine methyl ester (L-NAME) ( Figures 1 E and S2 ), which is consistent with the results of some human 15 and experimental animal studies. 16 However, blockade of cGMP signaling was reported to inhibit the cerebrovascular response to hypoxia, 17 and NO can also be produced by reduction of the nitrite anion (NO 2 − ), an alternative mechanism of NO generation by some heme- or molybdenum-cofactor-containing metalloproteins that can transfer an electron and facilitate proton donation.…”
Section: Resultssupporting
confidence: 90%
“…There is evidence that hypoxia-induced increases in cerebral blood flow are mediated by NO. 6 , 14 We found that in our experimental conditions, hypoxia-induced dilations of cortical arterioles in response to 10% inspired O 2 were unaffected by systemic NO synthase (NOS) blockade with N(ω)-nitro-L-arginine methyl ester (L-NAME) ( Figures 1 E and S2 ), which is consistent with the results of some human 15 and experimental animal studies. 16 However, blockade of cGMP signaling was reported to inhibit the cerebrovascular response to hypoxia, 17 and NO can also be produced by reduction of the nitrite anion (NO 2 − ), an alternative mechanism of NO generation by some heme- or molybdenum-cofactor-containing metalloproteins that can transfer an electron and facilitate proton donation.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, in hyperoxia [ 81 , 82 , 83 ], hypoxia [ 81 , 82 ], and hypercapnia [ 84 ], it was found to be an essential mediator of CBF in animal models. Moreover, NO also plays a leading role in coupling CBF and neuronal activity [ 85 ].…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%
“…Vasodilatory peptides include NO and acetylcholine. Vasoconstrictive peptides include the neuropeptide Y and serotonin[ 51 , 52 ].…”
Section: Autoregulation Of Cbfmentioning
confidence: 99%